Panel sequencing distinguishes monogenic forms of nephritis from nephrosis in children - Schapiro, David; Daga, Ankana; Lawson, Jennifer A.; Majmundar, Amar J.; Lovric, Svjetlana; Tan, Weizhen; Warejko, Jillian K.; Fessi, Inés; Rao, Jia; Airik, Merlin; Gee, Heon Yung; Schneider, Ronen; et al. (Nephrology Dialysis Transplantation, 2019)
Background. Alport syndrome (AS) and atypical hemolytic- uremic syndrome (aHUS) are rare forms of chronic kidney disease (CKD) that can lead to a severe decline of renal function. Steroid-resistant nephrotic syndrome (SRNS) is more common than AS and aHUS and causes 10% of childhood-onset CKD. In recent years, multiple monogenic causes of AS, aHUS and SRNS have been identified, but their relative prevalence has yet to be studied together in a typical pediatric cohort of children with proteinuria and hematuria. We hypothesized that identification of causative mutations by whole exome sequencing (WES) in known monogenic nephritis and nephrosis genes would allow distinguishing nephritis from nephrosis in a typical pediatric group of patients with both proteinuria and hematuria at any level. Methods. We therefore conducted an exon sequencing (WES) analysis for 11 AS, aHUS and thrombotic thrombocytopenic purpura-causing genes in an international cohort of 371 patients from 362 families presenting with both proteinuria and hematuria before age 25 years. In parallel, we conducted either WES or high-throughput exon sequencing for 23 SRNS-causing genes in all patients. Results. We detected pathogenic mutations in 18 of the 34 genes analyzed, leading to a molecular diagnosis in 14.1% of families (51 of 362). Disease-causing mutations were detected in 3 AS-causing genes (4.7%), 3 aHUS-causing genes (1.4%) and 12 NS-causing genes (8.0%). We observed a much higher mutation detection rate for monogenic forms of CKD in consanguineous families (35.7% versus 10.1%). Conclusions. We present the first estimate of relative frequency of inherited AS, aHUS and NS in a typical pediatric cohort with proteinuria and hematuria. Important therapeutic and preventative measures may result from mutational analysis in individuals with proteinuria and hematuria.
Created from Fastlane, Scopus look-up
Keywords: genetics; monogenic renal disease; nephritis; nephrotic syndrome; pediatrics